Pregnancy With Severe Thrombocytopenia Caused by HELLP Syndrome and Acute Idiopathic Thrombocytopenic Purpura: a Case Report - Widowati, Ayu Rizky; Firdaus, Wildan Aulia; Hariyati, Suheni Ninik; Hermanto, Djoko Heri (Asian Journal of Health Research, 2025)
Introduction: Thrombocytopenia in pregnancy could result in a wide range of prognosis, with the worst-case being life-threatening. Thrombocytopenia in pregnancy is a rare condition which could result in bleeding, endangering both maternal and foetal components. During pregnancy, thrombocytopenia could be caused by various factors, including idiopathic thrombocytopenic purpura and preeclampsia. Case Presentation: A 28-year-old pregnant woman, primigravid, gestational age 37-38 weeks old, single pregnancy, presents with fever ongoing for 12 days. A routine blood test returned a thrombocyte count of 11000/mm3. Patient received 8 units of thrombocyte concentrate with no improvement and progressive decline of thrombocyte count. Patient was assessed with severe thrombocytopenia caused by suspected dengue fever, with differential diagnoses being HELLP syndrome and idiopathic thrombocytopenic purpura. Patient was also assessed with severe preeclampsia and severe oligohydramnios. Patient’s condition improved after termination of pregnancy by caesarean section, accompanied with gradual return to normal thrombocyte count value. Conclusion: Thrombocytopenia in pregnancy could be caused by various factors, necessitating the need for a thorough medical evaluation to determine the underlying cause. A multidisciplinary and collaborative approach is highly recommended in managing pregnant women with thrombocytopenia.